PGE2 Elevates IL-23 Production in Human Dendritic Cells via a cAMP Dependent Pathway - Quanxing Shi; Zhao Yin; Bei Zhao; Fei Sun; Haisheng Yu; Xiangyun Yin; Liguo Zhang; Shouli Wang (Mediators of Inflammation)
PGE2 elevates IL-23 production in mouse dendritic cells while inhibits IL-23 production in isolated human monocytes. Whether this differential effect of PGE2 on IL-23 production is cell-type- or species-specific has not been investigated in detail. The present study was designed to investigate the effect of PGE2 on IL-23 production in human DCs and the possible underlying mechanisms. Human monocytes derived dendritic cells (Mo-DCs) were pretreated with or without PGE2. Then the cells were incubated with zymosan. Our results demonstrated that PGE2 promoted zymosan-induced IL-23 production in a concentration dependent manner. In addition, it was found that PGE2 is also able to elevate MyD88-mediated IL-23 p19 promoter activity. More importantly, ELISA data demonstrated that db-cAMP, a cAMP analog, and forskolin, an adenylate cyclase activator, can mimic the effect of PGE2 on zymosan-induced IL-23 production, and rp-cAMP, a protein kinase A (PKA) inhibitor, can block the effect of PGE2. Moreover, PGE2 can increase zymosan-induced expression of the mRNA levels of both p19 and p40 subunits, which was mimicked by db-cAMP and forskolin. Our data suggest that PGE2 elevates the production of IL-23 in human Mo-DCs via a cAMP dependent pathway.